The Influence Of The Location Of Concrete Joints And Longitudinal Reinforcement On T-Beams At A Distance Of A Quarter Of The Span - Aditama, Vega (Paulus Civil Engineering Journal, 2025)
The purpose of this study is to compare continuous beams (CB) with beams with concrete and reinforcement joints spaced at 1/4 span to analyze the flexural and shear behavior of reinforced concrete T-beams.  The bending moment, shear strength, and strain on each beam are measured experimentally as part of the procedures.  The test findings demonstrate that the T-beam with no joints has a larger flexural capacity, with a maximum bending moment of 28905926.28 Nmm and beginning cracking at a weight of 1543.08 kg.